An investigation of a novel LuGre-based friction force model. (December 2021) - Marques, Filipe; Woliński, Łukasz; Wojtyra, Marek; Flores, Paulo; Lankarani, Hamid M.
Abstract: The LuGre friction force models are amongst the most popular and powerful approaches to treat frictional contact in modeling, simulation and control of mechanical systems. However, these friction force models have some numerical difficulties related to physical inconstancies, when the systems under analysis include frictional contacts with significant variations in the normal loads. The LuGre friction force models can exhibit some problems resulting in the ratio between the friction and normal contact forces exceeding the friction coefficients. Another limitation deals with the drift problem which might occur during sticking periods. Thus, this work is aimed at presenting a new investigation based on the LuGre friction foundation capable of overcoming those limitations. In a simple manner, the new solution for the LuGre friction force model includes a stiffness coefficient to adjust and accommodate the variations of the normal contact forces in dynamical systems. In this study, two LuGre friction force models are revisited to facilitate the description of the proposed solution. Finally, several numerical application examples regarding a block of mass on a horizontal plane are presented to compare and examine the advantages and potentials of the original, amended and proposed models.